2016
DOI: 10.3892/or.2016.4858
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete radiofrequency ablation accelerates proliferation and angiogenesis of residual lung carcinomas via HSP70/HIF-1α

Abstract: Radiofrequency ablation (RFA) therapy has been proved effective and feasible for lung cancer. However, the molecular mechanisms of local lung cancer recurrence following RFA are poorly understood. The present study aimed to evaluate the ability of HSP70/HIF-1α to affect the proliferation and angiogenesis of non-small cell lung cancers (NSCLCs) following insufficient RFA to uncover the molecular mechanisms of local recurrence. In vitro heat treatment was used to establish sublines of NCI-H1650 cells. The NCI-H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Thus, thermal ablation will destroy the cellular and vasculature structures, which results in a new ablated tissue with different characteristics. However, the main limitation and challenge of thermal ablation is the risk of local recurrence and residual tumor after the thermal ablation, particularly at the tumor periphery 3 5 . The experimental studies showed that the combination therapy through local release of anticancer drugs from a miniaturized implant in solid tumors following thermal ablation can result in a better therapeutic efficacy by destroying the residual cancer cells and preventing tumor recurrence 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, thermal ablation will destroy the cellular and vasculature structures, which results in a new ablated tissue with different characteristics. However, the main limitation and challenge of thermal ablation is the risk of local recurrence and residual tumor after the thermal ablation, particularly at the tumor periphery 3 5 . The experimental studies showed that the combination therapy through local release of anticancer drugs from a miniaturized implant in solid tumors following thermal ablation can result in a better therapeutic efficacy by destroying the residual cancer cells and preventing tumor recurrence 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As a minimally invasive approach, RFA has been widely used as the favorable therapeutic strategies for lung cancer patients when surgical resections are not feasible. The major problem with RFA is that an exaggerated systemic inflammatory response may occur during treatment [ 5 , 6 ]. It has been reported that RFA can induce cytokine production, which may alter the local and systemic immune environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al . found that incomplete RFA treatment promoted HSP70 and HIF-1α expression in the transition area 17 . HSP70 interfered with the signaling pathways and cellular responses to hypoxic stress and influenced the stability of HIF-1α 18 .…”
Section: Introductionmentioning
confidence: 94%